Case report: Successful treatment of recurrent E. coli infection with bacteriophage therapy for patient suffering from chronic bacterial prostatitis - Johri, Apurva Virmani; Johri, Pranav; Hoyle, Naomi; Nadareishvili, Lia; Pipia, Levan; Nizharadze, Dea (Frontiers in Pharmacology, 2023)
Background: Chronic Bacterial Prostatitis (CBP) is inflammation of the prostate caused by bacterial infection. An estimated 8.2% of men have prostatitis, most commonly under the age of 50. Antibiotics often fail to treat CBP due to presence of bacterial biofilms and rising antibiotic resistance of pathogenic bacterial strains. The multidrug resistant (MDR) bacterial strains often implicated in cases of CBP include Extended Spectrum Beta Lactam resistant Escherichia coli, Vancomycin resistant Enterococci, gram-positive bacterial strains like Staphylococci and Streptococci, Enterobacteriaceae like Klebsiella and Proteus, and Pseudomonas aeruginosa.CBP patients experience significant deterioration in quality of life, with impact on mental health comparable with patients of diabetes mellitus and chronic heart failure, leading patients to explore alternatives like phage therapy.We present the case of a patient diagnosed with and exhibiting typical symptoms of CBP. Tests of the prostatic and seminal fluids identified E. coli as the causative pathogen. The patient did not experience favourable long-term treatment outcomes despite repeated antibiotic courses administered over five years. This led him to seek phage therapy for treatment of his condition.The cultured strain of E. coli was tested against bacteriophage preparations developed by the Eliava Institute, Georgia. Preparations showing lytic activity against the strain were used for the patient's treatment at the Eliava Phage Therapy Center (EPTC). The patient underwent two courses of treatment with the EPTC. The first treatment course resulted in significant symptomatic improvement, followed by complete resolution of symptoms post the second course of phage therapy.Samples tested during treatment showed declining bacterial growth, corresponding with symptomatic improvement. Post-treatment cultures had no growth of pathogenic bacteria.Discussion: This case illustrates the efficacy of bacteriophages in treating CBP, a condition that is often resistant to antibiotic therapies. Antibiotics such as ofloxacin, Fosfomycin, trimethoprim, nitrofurantoin and ceftriaxone were administered in multiple courses over five years, but the infection recurred after each course. After two courses of phage therapy, the patient experienced long-term symptom resolution and substantial reduction in bacterial load. Increasing numbers of such cases globally warrant further research into the potential for bacteriophages for treating MDR and chronic infections.